Prevalence of obesity and its correlates in school going adolescents of Haldwani, Nainital, Uttarakhand, India - Aggarwal, Shantanu; Awasthi, Sadhana; Singh, Rajesh Kumar; Rawat, Chandramohan Singh; Shukla, Saurabh; Akhtar, Farha (Indian Journal of Community Health, 2016)
Background: With a rising trend of Non-Communicable Diseases (NCDs) in the present world, overweight and obesity has gained importance as it is not only a disease in itself but also risk factor for majority of other NCDs. A dramatic increase in overweight and obesity among children and adolescent has raised the concern of various public health physicians especially in developing country like India. Aims & Objective: To study the prevalence of overweight and obesity & its correlates among school going adolescents of Haldwani block. Material & Methods: School based cross sectional study was done among the adolescents of 8th to 12th standard. To calculate the maximum sample size prevalence of obesity was assumed to be 50%, taking absolute error of 5%, design effect of 2 and 10% non-response rate the sample was calculated to be 880, rounded off to 900. Samples were collected from 30 clusters/schools using simple random sampling. Data was collected using a pre-designed, semi-structured and pre-tested questionnaire and analyzed by using SPSS version 22. Results: Prevalence of overweight and obesity was 13% (CI = 10.8 - 15.2%). Overweight and obesity was found to be significantly associated with urban area, private school, Socio-economic class I, non-vegetarian diet, physical inactivity and playing videogames, working on laptops and computer on univariate analysis. On applying binary logistic regression factors like private schools, socioeconomic class I, non-vegetarian diet and physical inactivity were again found to be significantly associated with overweight and obesity. Conclusion: Prevalence of obesity was found to be more in adolescents having modifiable risk factors.